Subjective Assessment of Concert Halls: a Common Vocabulary for Music Lovers and Acousticians - GIMENEZ, Alicia; CIBRIAN, Rosa Marıa; CERDA, Salvador (Archives of Acoustics, 2012)
In recent years we have interviewed members of the audience after musical performances and askedthem to evaluate the acoustics of the concert halls. A group of ‘music lovers’ (with a high level of musicaltraining and experience) and ‘acousticians’ (with a wide knowledge of the physical characteristics of soundtransmission) also attended each performance and answered the same questions as the general public.This group thereby served as a control group when evaluating surveys of the general public. In this paper,the results obtained when analyzing these control group surveys are presented. This analysis shows thata common vocabulary exists between music lovers and acousticians when rating a hall, although thegrouping of the questions for each factor depends on the training of the respondents.